How to determine the demand of aesthetic service - Visnu, Jodi (Penerbit Atma Jaya Catholic University of Indonesia, 2018)
BACKGROUND: Aesthetic service is one of tertiary needs in life but it has been concerned as primary needs for some individuals in the population recently. Many various products are developed and proposed by aesthetic center, with occasionally dramatic range of cost. In accordance with the aim to survive in this business competition, market identification can be done by watching client’s preferences when choosing an aesthetic clinic. METHODS: This is observational-analysis study with quantitative measurement and cross-sectional method. The following attributes were chosen by a preselection of 26 randomly selected patients: cost of the products, travel time, experience of the aesthetic physician, method of referral, and easy to communicate / to consult. The attributes were then divided into 13 levels. Using a random factor conducted by conjoint analysis through a program, 16 different scenarios of aesthetic clinic were created and rated by 96 randomly selected patients, they could rate these scenarios on a scale from 1 to 7 with respect to the likeliness of visiting the aesthetic clinic. RESULTS: The most important atribut was easy to communicate / to consult (37,1 percent), experience of the aesthetic physician (30,4 percent), travel time (15,8 percent), method of referral (10,5 percent), and cost of the products (6,1 percent). Six of 13 levels gave a negative influence on the decision making. CONCLUSIONS: The study shows that the two most important attributes are easy to  communicate / to consult and experience of the aesthetic physician. Another attributes are travel time, method of referral, and cost of the products. Conjoint analysis may help to determine client’s preferences. It also shows which levels positively or negatively contribute in every attribute. KEYWORDS: Conjoint analysis, preference, aesthetic medicine.